Enhancing Student Engagement Through Social Media A School of Business Case Study - M. Glowatz; L. Bofin (European Alliance for Innovation (EAI), 2014)
While many universities have been deploying both electronic learning (eLearning) and social media applications for academic purposes, there is currently little research on the impact on their use on students' overall learning experiences and associated learning possibilities. This paper elaborates on several online academic activities, such as Facebook, Twitter and quizzes for one classroom taught school of business undergraduate (UG) module. The similarities and differences discovered across all aspects of this paper's research findings are examined against Chickering & Gamson's [1] seven principles of good practice teaching and Astin's [2] five tenets of engagement. Online activities were tracked over a period of one academic semester (fifteen weeks) and results insinuate that innovative and sustainable social media can indeed be utilised in higher education to enhance student learning and engagement.